2017
DOI: 10.1177/1028315317697541
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Community College Internationalization Index

Abstract: To address the shortage of skilled workers in the 21st century, shifting demographics, competition for education funding, and the need to better serve underrepresented student populations, colleges and universities in the United States seek to increase internationalization efforts. While a number of instruments exist for measuring internationalization at the university level, few instruments are designed for measuring campus-level institutionalization, particularly at public community colleges. Moreover, curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…There is need to find effective tools for providing these opportunities to elevate the access for study abroad, cross-cultural training, and global engagement. Copeland, McCrink, and Starratt (2017) state that "internationalization processes were initially characterized as a component of student success … internationalization instead serves as a mechanism to student success. …internationalization is a set of methods by which to advance student success" (p. 366).…”
Section: Significance Of Studymentioning
confidence: 99%
“…There is need to find effective tools for providing these opportunities to elevate the access for study abroad, cross-cultural training, and global engagement. Copeland, McCrink, and Starratt (2017) state that "internationalization processes were initially characterized as a component of student success … internationalization instead serves as a mechanism to student success. …internationalization is a set of methods by which to advance student success" (p. 366).…”
Section: Significance Of Studymentioning
confidence: 99%
“…This framework also allows institutions to assess their internationalization progress along a continuum (e.g., seeking, building, reaching, and innovating) (CCID, 2015). Copeland, McCrink, and Starratt (2017) advanced Harder (2010) and Green and Siaya's (2005) work to create the Community College Internationalization Index (CCII), which incorporates contemporary shifts in internationalization efforts. This index seeks to measure internationalization efforts at the institution level for public community colleges (Copeland et al, 2017).…”
Section: Measuring Internationalization At Community Collegesmentioning
confidence: 99%
“…Copeland, McCrink, and Starratt (2017) advanced Harder (2010) and Green and Siaya's (2005) work to create the Community College Internationalization Index (CCII), which incorporates contemporary shifts in internationalization efforts. This index seeks to measure internationalization efforts at the institution level for public community colleges (Copeland et al, 2017). This tool allows institutions to track internationalization efforts while taking institutional context and community into account; a feature not present in Green and Siaya's 2005 instrument.…”
Section: Measuring Internationalization At Community Collegesmentioning
confidence: 99%
“…Table 1 displays tools suggested in current research to assess the quality of higher education through an international perspective. Copeland et al (2017) developed student development constructs related to student benefits of community college internationalisation, which reflect various activities and processes of multicultural interaction. Chavan et al (2014) suggested additional constructs of higher education service quality model by studying the expectations of eISSN: 2301-2218 Selection & Peer-review under responsibility of the Editors international and domestic students in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…institutional level (Copeland, McCrink, & Starratt, 2017). The quantitative instruments measuring internationalisation and its influence on the quality of higher education are claimed to be insufficient (Knight, 2011;Hudzik & Stohl, 2009).…”
Section: Introductionmentioning
confidence: 99%